COMPARISON OF THE ADDITION OF EM4 ACTIVATOR AND ORGANIC LEACHATE WATER IN COMPOSTING EMPTY BUNCHES PALM OIL - Husnawati Yahya; Alfis Yusri (Indonesian Journal of Environmental Sustainability, 2023)
Palm oil processing resulting empty fruit bunch waste that has a high organic content. Empty fruit bunches produce up to 6 million tons of waste per year and this waste has not been widely utilized so that can become an environmental problem such as pollution in the future. Alternative way to utilize the wastes is by converting them into organic fertilizer or compost. Therefore, this study aims to analyse and compare the results of EM4 activator composting by using leachate activators, the effect of composting time for each activator and the quality of compost referring to SNI 19-7030-2004. In this study, the composting process was carried out for 21 days with three experiments that include without treatment, by adding 1 litre of EM4 activator and by adding of 1 litre leachate water. The parameters measured were physical, temperature, humidity, pH, C, N, P, K and C/N-ratio. The results of this study indicate that composting with EM4 activator resulting composting pH level of 4.4 - 6.2, humidity of 1.5 - 70%, temperature of 29-38 °C, brownish black in colour, rough and hard in textures and soil-like (earthy) smell while composting using leachate water has a pH of 4.6 - 6.5, humidity of 3.9 - 80%, temperature of 29-38 °C and brownish black in colour, rough texture and slightly stink. Compost with EM4 activator was showing a faster composting time than using leachate. In term of quality, the composting by using EM4 activator produced higher quality compost compared to leachate activator composting with compost quality close to SNI 19-730-2004 requirement.